Yet another New Proof of Feuerbachs Theorem (Global Journal of Science Frontier Research, 2016)
In this article we give a new proof of the celebrated theorem of Feuerbach
Keywords: feuerbach’s theorem; stewart’s theorem; nine point center; nine point circle